A lead-free solder paste with low void rate and a preparation method thereof

By adding specific ratios of silver, copper, magnesium fluorosilicate, nanocarbon powder, rare earth oxides and flux to lead-free solder paste, the problem of high hollow rate in welding of traditional lead-free solder paste is solved, and the welding is improved Quality and reliability, suitable for high-precision welding, meet environmental protection requirements.

CN118720518BActive Publication Date: 2025-01-03DONGGUAN GAOHAILIANG METAL MATERIAL TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411059320.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-03
Publication Date
2025-01-03
Estimated Expiration
2044-08-03

AI Technical Summary

Technical Problem

Traditional lead-free solder paste is prone to hollows during the welding process, resulting in reduced solder strength, weakened reliability and short circuits in solder joints, affecting the welding quality.

Method used

Using the formulation of tin 70-90, silver 1-2, copper 3-6, magnesium fluorosilicate 2-5, nanocarbon powder 3-6, rare earth oxide 4-5 and flux 20-30, nanocarbon powder and rare earth oxides improve microstructure, magnesium fluorosilicate reduces surface tension, silver and copper improves conductivity and hardness, flux reduces bubbles and retention, and optimizes the amount of tin, silver and copper components to reduce solder joint size.

Benefits of technology

It significantly reduces the void rate, improves welding quality and reliability, enhances the firmness and durability of welded joints, and is suitable for high-precision welding and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004977348480000051
    Figure BDA0004977348480000051
  • Figure BDA0004977348480000061
    Figure BDA0004977348480000061
  • Figure BDA0004977348480000071
    Figure BDA0004977348480000071
Patent Text Reader

Abstract

The present application relates to the technical field of lead-free solder paste, and more specifically, to a lead-free solder paste with low voiding rate and precision welding and a preparation method thereof, which is prepared from the following raw materials in parts by weight: 70-90 parts of tin, 1-2 parts of silver, 3-6 parts of copper, 2-5 parts of magnesium fluorosilicate, 3-6 parts of nano-carbon powder, 4-5 parts of rare earth oxide and 20-30 parts of flux. The above formula can reduce the voiding rate in the welding process, improve the wettability of the lead-free solder paste, and improve the quality and reliability of the welding points.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lead-free solder paste, and more specifically, to a lead-free solder paste with low void rate and precision welding and a preparation method thereof. Background Art

[0002] Precision welding is a high-precision, high-quality welding technology, mainly used in fields with high requirements for welding quality and precision, such as aerospace, electronics, medical and other industries. Lead-free solder paste is often used for precision welding. Lead-free solder paste does not contain lead, so it is environmentally friendly and meets the requirements of current environmental regulations. At the same time, the welding effect of lead-free solder paste is usually good, and it can provide stable welding joints to ensure welding quality and reliability.

[0003] Traditional lead-free solder paste needs to reach a certain temperature to melt and form solder joints during the soldering process. However, lead-free solder paste contains different metal particles. The diffusion speeds of different metal particles after melting are inconsistent, and vacancies may be left in the intermetallic compound layer. These vacancies will gradually form voids as the aggregation process proceeds. Voids will reduce the effective soldering area, weaken the soldering strength, and reduce the soldering reliability. Secondly, voids may also push the solder, causing short circuits between solder joints, further affecting the soldering quality. Summary of the invention

[0004] In order to reduce the void rate of lead-free solder paste, the present application provides a lead-free solder paste with low void rate and a preparation method thereof.

[0005] In the first aspect, the present application provides a lead-free solder paste with low void ratio and precision welding, which adopts the following technical scheme: A lead-free solder paste with low void ratio and precision welding is prepared from the following raw materials in parts by weight:

[0006] Tin 70-90 parts

[0007] Silver 1-2 parts

[0008] Copper 3-6 parts

[0009] 2-5 parts of magnesium fluorosilicate

[0010] 3-6 parts of nano carbon powder

[0011] 4-5 parts of rare earth oxide

[0012] 20-30 parts of flux.

[0013] By adopting the above technical solution, the void rate in the welding process can be reduced, the wettability and stability of the lead-free solder paste can be improved, and the quality and reliability of the welding points can be improved.

[0014] Since the addition of nano-carbon powder and rare earth oxides helps to improve the microstructure and properties of solder paste, it is easier to spread evenly during the welding process, thereby reducing the generation of welding voids. At the same time, the addition of nano-carbon powder and rare earth oxides improves the strength and reliability of solder joints, making the welding joints more firm and durable. The addition of magnesium fluorosilicate, first, reduces the surface tension of solder paste, improves the wettability, fluidity and stability during welding; second, it reacts with oxides during welding to generate volatile gases, thereby removing oxides from the welding interface and improving welding quality. Silver has good electrical and thermal conductivity, which can improve the electrical properties of welding joints. At the same time, silver can also form alloys with tin, improve the antioxidant properties of solder paste, and extend the service life of welding joints. Adding an appropriate amount of copper can improve the hardness and wear resistance of solder paste, thereby improving the mechanical properties of welding joints. Copper can also form alloys with tin, reduce the melting point of solder paste, and improve the wettability and fluidity of the welding process. During the welding process, the flux plays a role in cleaning the welding surface, reducing the welding temperature, improving the welding quality, and improving the stability of lead-free solder paste. At the same time, flux can significantly reduce the surface tension of molten solder, making it easier for the solder to spread and wet on the welding interface, helping to reduce voids formed during the welding process due to poor solder flow.

[0015] At the same time, this application optimizes the dosage of main components such as tin, silver, and copper, so that the size of the solder joints is further reduced to meet the needs of high-precision soldering of existing electronic equipment.

[0016] Preferably, the soldering flux is prepared by the following method:

[0017] dissolving rosin and an active agent in a solvent to obtain a rosin solution;

[0018] Succinic acid amine salt, ethylhexyl isooctanoate, hydrogenated castor oil, ethylene bisstearamide and hydroxyethylidene diphosphonic acid are added to the rosin solution and stirred evenly to obtain a soldering flux.

[0019] Preferably, the weight parts of raw materials for preparing the soldering flux are as follows:

[0020] 10-20 parts of rosin

[0021] 1-2 parts of active agent

[0022] 30-40 parts of solvent

[0023] 1-2 parts of succinic acid amine salt

[0024] 1-3 parts of ethylhexyl isooctanoate

[0025] 3-5 parts hydrogenated castor oil

[0026] 1-3 parts of ethylene bisstearamide

[0027] 1-2 parts of hydroxyethylidene diphosphonic acid.

[0028] By adopting the above technical solution, the prepared flux can effectively reduce the generation and retention of bubbles during the welding process, thereby significantly reducing the welding void rate and improving the quality and reliability of the welding joint.

[0029] As the main component of flux, rosin has good wettability and fluidity, which helps the solder to spread evenly during the welding process and reduce the formation of voids. The activator can reduce the surface tension of the solder, improve the wettability of the solder and welding interface, and further reduce the generation of voids. At the same time, the activator can also improve the wettability, diffusibility and stability of lead-free solder paste. Additives such as succinic acid amine salt and ethylhexyl isooctanoate can remove oxides and impurities at the welding interface, reduce gas generation during welding, and thus reduce the void rate. Hydrogenated castor oil can improve the fluidity of solder, making it easier to fill the tiny gaps at the welding interface and reduce the formation of voids. Ethylene bisstearamide can optimize the lubricity of the welding interface, reduce the friction resistance during welding, and thus improve the welding quality. The addition of hydroxyethylidene diphosphonic acid may help improve the antioxidant properties of solder paste and prevent welding defects caused by oxidation during welding.

[0030] Preferably, the active agent is obtained by mixing diphenylguanidine hydrochloride and fatty acid in a weight ratio of (0.5-1):4.

[0031] By adopting the above technical solution, the lead-free solder paste can be better wetted and flowed during the soldering process, thereby covering the soldering area and forming uniform solder joints, while increasing the stability of the lead-free solder paste.

[0032] Preferably, the nano carbon powder is modified nano carbon powder, which is prepared by the following method:

[0033] A: Soak the carbon powder in a sodium hydroxide solution with a mass fraction of 10-15% to activate it, thereby obtaining activated carbon powder;

[0034] B: Dissolve succinic anhydride in ethanol, add activated carbon powder, stir under argon, raise the temperature to 50-60°C, add a mixture of 4,4-bipyridine and cuprous bromide, continue stirring under argon for 5-6 hours, and after the reaction is completed, rinse the reactant with deionized water, filter and dry to obtain modified nano carbon powder.

[0035] By adopting the above technical scheme, promoting the uniform dispersion of modified nano carbon powder in solder paste can reduce the agglomeration phenomenon during welding, ensure the uniform flow and wetting of solder, and thus reduce the void rate. At the same time, due to its higher surface activity, the modified nano carbon powder can more effectively combine with the metal ions in the lead-free solder paste, promote the formation of intermetallic compounds, and thus improve the quality of the welded joint. In step A, the carbon powder is activated by sodium hydroxide solution, and more active sites are formed on the surface of the carbon powder through chemical action, which is conducive to the subsequent modification reaction. In step B, succinic anhydride reacts chemically with the active sites on the surface of the carbon powder to change the surface properties of the carbon powder. Succinic anhydride reacts with the functional groups on the surface of the activated carbon powder to form new chemical bonds, which can improve the binding ability of metal ions in the lead-free solder paste. At the same time, a mixture of 4,4'-bipyridine and cuprous bromide participates in the reaction as a catalyst to promote the reaction.

[0036] Preferably, the weight ratio of the carbon powder, the succinic anhydride, the 4,4-bipyridine and the cuprous bromide is (3-6): (1-1.5): (0.2-0.3): 0.1.

[0037] By adopting the above technical scheme, the dosage of carbon powder, succinic anhydride, 4,4-bipyridine and cuprous bromide is optimized, the reaction of succinic anhydride and activated carbon powder is accelerated, and the reaction time is shortened.

[0038] Preferably, the nano carbon powder includes carbon powder with an average particle size of 20-30 nm and carbon powder with an average particle size of 50-100 nm.

[0039] By adopting the above technical solution and optimizing the average particle size of nano carbon powder, the viscosity of lead-free solder paste can be adjusted, the stability of lead-free solder paste can be improved, the welding quality of lead-free solder paste with low precision welding and void rate can be improved, and the void rate can be reduced.

[0040] Preferably, the rare earth oxide includes at least one of lanthanum oxide, cerium oxide, yttrium oxide, rubidium oxide, thulium oxide and europium oxide.

[0041] By adopting the above technical solution and optimizing the types of rare earth oxides, the wettability of lead-free solder paste can be improved, which helps the lead-free solder paste to better cover and wet the soldering substrate during the soldering process, thereby improving the soldering quality and reducing the void rate.

[0042] Preferably, the rare earth oxide is obtained by mixing lanthanum oxide and cerium oxide in a weight ratio of (2-5):1.

[0043] By adopting the above technical solution, the types of rare earth oxides are optimized, so that the rare earth oxides are dispersed more evenly in the lead-free solder paste, further improving the fluidity and wettability of the lead-free solder paste, so that the solder can cover the pad more evenly, reducing the possibility of air being trapped in the solder joint, thereby reducing the void rate.

[0044] In a second aspect, the present application provides a method for preparing a lead-free solder paste with low void rate and precision welding, which adopts the following technical solution:

[0045] A method for preparing a lead-free solder paste with low void rate and precision welding, comprising the following preparation steps:

[0046] S1, putting tin, silver, copper and nano carbon powder into a furnace, heating to 320-360°C to obtain alloy melt;

[0047] S2, the alloy melt is poured into an atomizing chamber protected by nitrogen, the rotation speed is 100,000 rpm, the air pressure is 110,000-120,000 Pa, and the alloy melt is sieved through a screening device to obtain alloy powder, the average particle size of the alloy powder is 15-25 microns;

[0048] S3, mixing raw materials such as alloy powder, magnesium fluorosilicate, rare earth oxide and flux evenly to obtain lead-free solder paste with low void rate and precision welding.

[0049] By adopting the above technical solution, the low void rate precision welding lead-free solder paste is mixed evenly, has good stability, can be stored for a long time, and has good wettability and weldability, and low void rate. After the tin is melted, the fluidity of the entire system is greatly increased, which is conducive to subsequent atomization.

[0050] In summary, this application has the following beneficial effects:

[0051] 1. Reduce the void rate: This lead-free solder paste effectively reduces the void rate during the welding process. Thanks to the addition of flux ingredients such as nano-carbon powder, rare earth oxides and magnesium fluorosilicate, it can remove oxides and impurities at the welding interface during the welding process and reduce the formation of voids.

[0052] 2. Improve welding performance: Tin, silver and copper as the main metal components ensure the fluidity and wettability during welding. Tin is the main performance of the welding material, while the appropriate addition of silver and copper further improves the electrical and mechanical properties of the welding joint.

[0053] 3. Precision welding: Because the solder paste has a low void rate and excellent welding performance, it is particularly suitable for precision welding scenarios. In the assembly of high-density electronic components, it can ensure the accuracy and consistency of the welding joints and improve the overall performance and reliability of the product.

[0054] 4. Environmental protection: Since the solder paste is lead-free, it will not release harmful lead fumes during the welding process, which helps to reduce pollution in the workplace and the environment and meets modern environmental protection requirements. DETAILED DESCRIPTION

[0055] Rosin was purchased from Jinan Boyang Chemical Co., Ltd., with a density of 1.060-1.085 g / cm 3 .

[0056] Hydrogenated castor oil was purchased from Guangzhou Aobosheng Chemical Co., Ltd. under the brand name BASF.

[0057] Preparation Example

[0058] Preparation Example 1

[0059] A soldering flux is prepared by the following method:

[0060] Dissolve 100 g of rosin and 10 g of an active agent (diphenylguanidine hydrochloride) in 30 g of a solvent (diglycidyl ether) to obtain a rosin solution;

[0061] Add 10 g of succinic acid amine salt, 10 g of ethylhexyl isooctanoate, 30 g of hydrogenated castor oil, 10 g of ethylene bisstearamide and 10 g of hydroxyethylidene diphosphonic acid to the rosin solution, stir evenly, and obtain a soldering flux.

[0062] The difference between Preparation Example 2-3 and Preparation Example 1 is that the types, amounts and experimental parameters of some raw materials for preparing the flux are different. The specific differences are shown in Table 1:

[0063] Table 1 Types, amounts and experimental parameters of raw materials for preparing flux in Preparation Examples 1-3

[0064]

[0065] Preparation Example 4

[0066] A soldering flux, the difference between this preparation example and preparation example 1 is that the activator is obtained by mixing diphenylguanidine hydrochloride and fatty acid in a weight ratio of 0.5:4.

[0067] Preparation Example 5

[0068] A soldering flux, the difference between this preparation example and preparation example 1 is that the activator is obtained by mixing diphenylguanidine hydrochloride and fatty acid in a weight ratio of 1:4.

[0069] Comparative Preparation Example

[0070] Comparative Preparation Example 1

[0071] A soldering flux, the difference between this preparation example and preparation example 1 is that the activator is omitted.

[0072] Comparative Preparation Example 2

[0073] A soldering flux, the difference between this preparation example and preparation example 1 is that: an equal amount of hydrogenated castor oil is replaced by epoxidized soybean oil.

[0074] Comparative Preparation Example 3

[0075] A soldering flux, the difference between this preparation example and preparation example 1 is that ethylhexyl isooctanoate is omitted.

[0076] Comparative Preparation Example 4

[0077] A soldering flux, the difference between this preparation example and preparation example 80.3 1 is that succinic acid amine salt is omitted.

[0078] Comparative Preparation Example 5

[0079] A soldering flux, the difference between this preparation example and preparation example 1 is that hydroxyethylidene diphosphonic acid is omitted.

[0080] Example

[0081] Example 1

[0082] A lead-free solder paste with low void rate and precision welding is prepared by the following method:

[0083] S1. Grind 10g of silver, 30g of copper and 30g of nano carbon powder into powder (average particle size is 5-10 microns), put 700g of tin, silver, copper, magnesium fluorosilicate and nano carbon powder into a furnace, heat to 320°C to obtain alloy melt;

[0084] S2, the alloy melt is poured into an atomizing chamber protected by nitrogen, the rotation speed is 100,000 rpm, the air pressure is 110,000 Pa, and the alloy melt is sieved through a screening device to obtain alloy powder, the average particle size of the alloy powder is 15-25 μm;

[0085] S1. The alloy powder, 40 g of magnesium fluorosilicate, 30 g of rare earth oxide (lanthanum oxide) and 200 g of flux (from Preparation Example 1) are mixed evenly to obtain a lead-free solder paste for precision welding with low void rate.

[0086] The difference between Example 2-3 and Example 1 is that the types, amounts and experimental parameters of some raw materials for preparing lead-free solder paste with low void rate precision welding are different. The specific differences are shown in Table 2:

[0087] Table 2 Types, amounts and experimental parameters of raw materials for preparing lead-free solder paste with low void rate in Examples 1-3

[0088]

[0089]

[0090] Example 4

[0091] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 1 is that the soldering flux comes from comparative example 4.

[0092] Example 5

[0093] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 1 is that the soldering flux comes from comparative example 5.

[0094] Example 6

[0095] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 1 is that the soldering flux comes from preparation of comparative example 1.

[0096] Example 7

[0097] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 1 is that the soldering flux comes from preparation comparative example 2.

[0098] Example 8

[0099] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 1 is that the soldering flux comes from preparation comparative example 3.

[0100] Example 9

[0101] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 1 is that the soldering flux comes from preparation comparative example 4.

[0102] Example 10

[0103] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 1 is that the soldering flux comes from preparation comparative example 5.

[0104] Embodiment 11

[0105] A lead-free solder paste with low void rate and precision welding, the difference between this embodiment and embodiment 1 is that the nano carbon powder is modified nano carbon powder, which is prepared by the following method:

[0106] A: 30 g of carbon powder was immersed in a 10% sodium hydroxide solution for activation to obtain activated carbon powder;

[0107] B: Dissolve 10 g of succinic anhydride in 100 g of ethanol, add activated carbon powder, stir under argon, raise the temperature to 50°C, add a mixture of 2 g of 4,4-bipyridine and 1 g of cuprous bromide, continue stirring under argon for 5 hours, after the reaction is completed, rinse the reactant with deionized water, filter and dry to obtain modified nano carbon powder.

[0108] Example 12

[0109] A lead-free solder paste with low void rate and precision welding, the difference between this embodiment and embodiment 1 is that the nano carbon powder is modified nano carbon powder, which is prepared by the following method:

[0110] A: 60 g of carbon powder was immersed in a 15% sodium hydroxide solution for activation to obtain activated carbon powder;

[0111] B: Dissolve 15 g of succinic anhydride in 150 g of ethanol, add activated carbon powder, stir under argon, heat to 60°C, add a mixture of 3 g of 4,4-bipyridine and 1 g of cuprous bromide, continue stirring under argon for 6 hours. After the reaction is completed, rinse the reactant with deionized water, filter and dry to obtain modified nano carbon powder.

[0112] Example 13

[0113] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 1 is that the nano carbon powder includes carbon powder with an average particle size of 20 nm and carbon powder with an average particle size of 50 nm.

[0114] Embodiment 14

[0115] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 11 is that the nano carbon powder includes carbon powder with an average particle size of 30 nm and carbon powder with an average particle size of 50 nm.

[0116] Embodiment 15

[0117] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 1 is that the rare earth oxide is obtained by mixing lanthanum oxide and cerium oxide in a weight ratio of 2:1.

[0118] Example 16

[0119] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 1 is that the rare earth oxide is obtained by mixing lanthanum oxide and cerium oxide in a weight ratio of 5:1.

[0120] Embodiment 17

[0121] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 9 is that pure water is used instead of an equal mass of sodium hydroxide.

[0122] Embodiment 18

[0123] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 11 is that pure water is used instead of an equal mass of succinic anhydride.

[0124] Embodiment 19

[0125] A lead-free solder paste for precision welding with low void rate. The difference between this embodiment and embodiment 11 is that pure water is used instead of an equal mass of 4,4-bipyridine.

[0126] Embodiment 20

[0127] A lead-free solder paste with low void rate and precision welding. The difference between this embodiment and embodiment 11 is that pure water is used instead of cuprous bromide of equal mass.

[0128] Comparative Example

[0129] Comparative Example 1

[0130] A lead-free solder paste for precision welding with low void rate, the difference between this comparative example and Example 1 is that magnesium fluorosilicate is omitted.

[0131] Comparative Example 2

[0132] A lead-free solder paste for precision welding with low void rate, the difference between this comparative example and Example 1 is that the nano carbon powder is omitted.

[0133] Comparative Example 3

[0134] A lead-free solder paste for precision welding with low void rate, the difference between this comparative example and Example 1 is that rare earth oxide is omitted.

[0135] Comparative Example 4

[0136] A lead-free solder paste for precision welding with low void rate, the difference between this comparative example and Example 1 is that silver is omitted.

[0137] Comparative Example 5

[0138] A lead-free solder paste for precision welding with low void rate, the difference between this comparative example and Example 1 is that copper is omitted.

[0139] Performance testing

[0140] The lead-free solder paste with low void ratio and precision welding prepared in Examples 1-20 and Comparative Examples 1-5 was subjected to void ratio test, stability test and expansion ratio test.

[0141] Detection method / test method Void test: The void rates of solder joints formed by low-precision soldering of lead-free solder paste in Examples 1-20 and Comparative Examples 1-10 were measured respectively by section microscopic observation.

[0142] Stability test: Store at 25℃, test the viscosity once a month. Compared with the initial viscosity, if the viscosity value increases by less than 10Pa.s, it is considered normal. If the viscosity value increases by 13-16Pa.s, it is considered deteriorated. If the viscosity value increases by 29-32Pa.s, it is considered scrapped.

[0143] Expansion rate: The expansion rate test is carried out according to JIS Z 3197 standard. The greater the expansion rate, the better the wetting performance.

[0144] Welding performance: Refer to the test method of SJ / T11186-199 "General Specification for Tin-Lead Paste Solder". The experimental results are shown in Table 3:

[0145] Table 3 Experimental data of Examples 1-20 and Comparative Examples 1-5

[0146]

[0147]

[0148] From Examples 1-20 and Comparative Examples 1-5 in combination with Table 3, it can be seen that the lead-free solder paste with low void rate and precision welding is prepared by the present application, which produces fewer voids during welding and has good welding quality, and the lead-free solder paste with low void rate and precision welding has good wetting performance and stability.

[0149] By comparing Example 1 with Comparative Examples 1-5, in the void test experiment, the void rate of Comparative Examples 1-5 is significantly higher than that of Example 1; in the expansion rate test, the expansion rates of Comparative Examples 1-5 are significantly lower than those of Example 1; the welding performance in Example 1 is good, the welding performance of Comparative Examples 1-3 is poor, and the welding performance of Comparative Examples 4-5 is average. It can be seen that the low void rate precision welding lead-free solder paste prepared by the formula in the present application has the advantages of low void distance, good wettability and good welding performance.

[0150] By comparing Example 1 with Examples 4-5, the void rate of Example 4-5 in the void test is lower than that of Example 1; in the stability test, Examples 4-5 still maintain normal phenomena in May; in the expansion rate test, the expansion rates of Examples 4-5 are significantly higher than those of Example 1, indicating that the void rate of the solder paste can be reduced and the stability and wettability of the solder paste can be improved by mixing diphenylguanidine hydrochloride and fatty acid.

[0151] By comparing Example 1 with Examples 6-10, the void rate of Example 6-10 in the void test is higher than that of Example 1; in the stability test, Examples 6-7 and 10 were scrapped in February; in the expansion rate test, the expansion rates of Examples 6-10 were significantly lower than those of Example 1; the welding performance of Examples 6-10 was average;

[0152] It can be seen from Examples 1, 4-5 and 6-10 that the soldering flux prepared by the formula in the present application can greatly reduce the void rate of the solder paste and improve the stability, wettability and welding performance of the solder paste.

[0153] By comparing Example 1 with Examples 11-12, in the void test, the void ratio of Examples 11-12 is significantly lower than that of Example 1; in the expansion rate test, the expansion rates of Examples 11-12 are significantly higher than that of Example 1;

[0154] By comparing Example 11 with Examples 17-20, in the void test, the void ratio of Examples 17-20 is significantly lower than that of Example 11; in the expansion ratio test, the expansion ratio of Examples 17-20 is significantly lower than that of Example 1; the welding performance of Examples 17-20 is average;

[0155] Compared with Examples 1, 11-12 and 17-20, the modified nano carbon powder prepared by the formulation and method of the present application can effectively reduce the void rate of the solder paste and improve the wettability and welding performance of the solder paste.

[0156] Comparing Example 1 with Example 13, in the void test, the void rate of Example 13 is significantly lower than that of Example 1; in the expansion rate test, the expansion rate of Example 13 is significantly lower than that of Example 1, indicating that by combining nano-carbon powders with different average particle sizes, the void rate of the solder paste can be further reduced and the wettability of the solder paste can be improved.

[0157] Comparing Example 1 with Examples 15-16, in the void test, the void rate of Examples 15-16 is lower than that of Example 1; in the expansion rate test, the expansion rates of Examples 15-16 are significantly lower than those of Example 1, indicating that by combining different types of rare earth oxides, the void rate of the solder paste can be further reduced and the wettability of the solder paste can be improved.

[0158] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A lead-free solder paste with low void rate and precision welding, characterized in that: Prepared from the following raw materials in parts by weight: Tin 70-90 parts Silver 1-2 parts Copper 3-6 parts 2-5 parts of magnesium fluorosilicate 3-6 parts of nano carbon powder 4-5 parts of rare earth oxide 20-30 parts of flux; The soldering flux is prepared by the following method: dissolving rosin and an active agent in a solvent to obtain a rosin solution; Add succinic acid amine salt, ethylhexyl isooctanoate, hydrogenated castor oil, ethylene bisstearamide and hydroxyethylidene diphosphonic acid to the rosin solution, stir evenly, and obtain a soldering flux; The weight parts of raw materials for preparing the soldering flux are as follows: 10-20 parts of rosin 1-2 parts of active agent 30-40 parts of solvent 1-2 parts of succinic acid amine salt 1-3 parts of ethylhexyl isooctanoate 3-5 parts hydrogenated castor oil 1-3 parts of ethylene bisstearamide 1-2 parts of hydroxyethylidene diphosphonic acid.

2. The lead-free solder paste with low void ratio according to claim 1, characterized in that: The active agent is obtained by mixing diphenylguanidine hydrochloride and fatty acid in a weight ratio of (0.5-1):

4.

3. The low-voiding precision soldering lead-free solder paste according to claim 1, characterized in that: The nano carbon powder is a modified nano carbon powder, which is prepared by the following method: A: Soak the carbon powder in a sodium hydroxide solution with a mass fraction of 10-15% to activate it, and obtain activated carbon powder; B: Dissolve succinic anhydride in ethanol, add activated carbon powder, stir under argon, raise the temperature to 50-60°C, add a mixture of 4,4-bipyridine and cuprous bromide, continue stirring under argon for 5-6 hours, after the reaction is completed, rinse the reactant with deionized water, filter and dry to obtain modified nano carbon powder.

4. The low void rate lead-free solder paste for precision welding according to claim 3, characterized in that: The weight ratio of the carbon powder, the succinic anhydride, the 4,4-bipyridine and the cuprous bromide is (3-6): (1-1.5): (0.2-0.3): 0.

1.

5. The low void ratio lead-free solder paste for precision welding according to claim 1, characterized in that: The nano carbon powder includes carbon powder with an average particle size of 20-30 nm and carbon powder with an average particle size of 50-100 nm.

6. The low void rate lead-free solder paste for precision welding according to claim 1, characterized in that: The rare earth oxide includes at least one of lanthanum oxide, cerium oxide, yttrium oxide, rubidium oxide, thulium oxide and europium oxide.

7. The low void ratio lead-free solder paste for precision welding according to claim 6, characterized in that: The rare earth oxide is obtained by mixing lanthanum oxide and cerium oxide in a weight ratio of (2-5):

1.

8. A method for preparing a lead-free solder paste with low void ratio as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: S1, putting tin, silver, copper and nano carbon powder into a furnace, heating to 320-360°C to obtain alloy melt; S2, atomizing the alloy solution into alloy powder by nitrogen protection atomization method, wherein the average particle size of the alloy powder is 15-25 microns; S3, the alloy powder, magnesium fluorosilicate, rare earth oxide and flux raw materials are mixed evenly to obtain a lead-free solder paste with low void rate and precision welding.

Citation Information

Cited By

  • High-performance lead-free solder paste and preparation method and application thereof

    CN120095403A

  • High-performance lead-free tin paste, preparation method and application thereof

    CN120095403B

  • Soldering flux, low-voidage high-lead soldering paste and preparation method of soldering flux

    CN121267469A

  • A soldering flux, a low-cavity high-lead soldering paste and a preparation method thereof

    CN121267469B